The least innovative regions in Poland and in France in the process of smart specialisation - Anna Golejewska; Dorota Czyżewska (European Regional Science Association (ERSA), 2015)
The notion of smart specialisation is an important framework in the structural funding period 2014-2020. Although the original academic concept of this policy was sectorally oriented and focused on the productivity gap between the EU and the US, it is increasingly applied to regional innovation context [OECD 2013; Foray, David, Hall 2009; McCann, Ortega-Argiles 2013; Camagni, Capello 2013]. Regions are recognized as a relevant level of innovation policies given the weight of agglomeration economies. Smart policies build the knowledge-based development potential of any region, strong or weak, high-tech or low-tech. According to smart specialisation approach, those regions which are not leaders in any of the major science and technology areas, should follow the rule: not to do everything in science, technology and innovation and to promote actions making their knowledge base unique and superior to others. The progress of identifying regional smart specialisations is diverse in selected Polish and French regions. The empirical analysis has shown that there is not great difference in the selection methods of smart specialisations implemented by catching-up regions in Poland and the best performing developed regions in France [Czyżewska, Golejewska 2014]. The main objective of the paper is to assess the advancement of the least innovative Polish and French regions in the process of smart specialisation. In order to achieve the main objective of the paper, the following detailed objectives are expected to be met: - presentation of the economic fundamentals of smart specialisation; - presentation of literature review of challenges for the least developed regions in Europe; - selection of the least innovative Polish and French regions on the basis of four indicators: GDP per capita, population aged 25-64 with tertiary education attainment, R&D expenditure and patent applications to the EPO. - assessment of the advancement of the smart specialisation process in selected regions with reference to their economic, social and innovation potential. As research methods, the authors used descriptive analysis, analysis of strategic documents, case studies analysis and statistical analysis. The statistical analysis is based on Eurostat Regional Statistics. The lack of actual and comparable regional data for the whole group of regions caused the choice of the year 2011, as the reference year. In case of patent applications the last analyzed year was the year 2010. It is expected that the research results concerning the advancement of the smart specialisation process in selected regions under analysis will give recommendations for regional authorities of Polish and French regions in terms of the smart specialisation elaboration and monitoring.
Keywords: R58; L52; 330; national and regional smart specialisation; innovation policy; France; Poland